Anti-TNF agents for the treatment of active non-radiographic axial spondyloarthritis - I. Olivieri; Salvatore D'Angelo; C. Palazzi; P. Leccese; A. Nigro; A. Padula (Reumatismo, 2013)
The spondyloarthritis (SpA) complex includes ankylosing spondylitis (AS), reactive arthritis, psoriatic arthritis, arthritis related to inflammatory bowel disease and forms that do not meet established criteria for these definite categories which are designated as undifferentiated SpA. In the early 1990s, two sets of classification criteria were suggested with the purpose to cover the whole clinical spectrum of SpA: the Amor criteria and the European Spondylarthropathy Study Group (ESSG) criteria...